2020
DOI: 10.1111/ijac.13616
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes and their thermal conductivities of MgO crystals containing various impurities (B, Ca, Si)

Abstract: MgO is industrially produced from seawater or dolomite as the raw material. MgO synthesized from seawater has a relatively low impurity concentration. However, these impurities strongly affect the fine structure and physical properties (especially the thermal conductivity) of MgO. In this research, the influence of impurity concentration on the MgO grain growth and its thermal conductivity was investigated. The processing conditions for MgO powder synthesis were optimized by a polymer complex method using magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Magnesium oxide (MgO) has an immensely important attractive characteristics: high melting point (~ 2800 o C) [1][2][3][4], good chemical resistance [4][5][6], low dielectric constant [7,8], high electrical resistance [5], low thermal conductivity [6], and nontoxicity [9]. It is used in many application fields [10] such as in cement production [1,4,11,12], refractories elaboration [4,13], water purification [14], as an antibacterial material [7,15], biomaterial [16], in pharmaceuticals and cosmetics [7], in paints [17,18],…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium oxide (MgO) has an immensely important attractive characteristics: high melting point (~ 2800 o C) [1][2][3][4], good chemical resistance [4][5][6], low dielectric constant [7,8], high electrical resistance [5], low thermal conductivity [6], and nontoxicity [9]. It is used in many application fields [10] such as in cement production [1,4,11,12], refractories elaboration [4,13], water purification [14], as an antibacterial material [7,15], biomaterial [16], in pharmaceuticals and cosmetics [7], in paints [17,18],…”
Section: Introductionmentioning
confidence: 99%
“…High thermal conductivity is another significant advantage of MgO ceramic. It was reported that the thermal conductivity of MgO ceramic with 100% relative density was 38 W/(m K) 17 . However, the sintering temperatures of most MgO‐based ceramics were higher than 1000°C, making them unsuitable for the LTCC technology.…”
Section: Introductionmentioning
confidence: 99%